Analisis Penerapan E-Filling Dimasa Pandemi Covid 19 Sebagai Upaya Meningkatkan Kepatuhan Wajib Pajak Orang Pribadi - Rusli Amrul (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2021)
The purpose of this research is to determine the application of e-filling during the pandemic in increasing individual taxpayer compliance in submitting annual tax. The data analysis technique used in this study is a qualitative descriptive analysis method, namely by collecting data, processing data, analyzing data, conclude and providing interpretation. The results of the study are Tax Service Office in West Mataram in implementing e-filling during the covid 19 pandemic has been in accordance with the procedures based on tax laws and regulations on tax administration. The implementation of social distancing during the COVID-19 pandemic is one of the obstacles in disseminating the form of tax annual reports to taxpayers through e-filling. The compliance of individual taxpayers during the COVID-19 pandemic in reporting annual tax through e-filing is more constrained because individual taxpayers mostly report annual tax at the end of the reporting deadline, not all taxpayers understand technology such as computers, internet access and email, lack of knowledge of individual taxpayers in filling out annual tax report online so that there are many errors in filling out annual tax report. The network system on the website of the Directorate General of Taxes is often disrupted due to too many individual taxpayers accessing the website in the month of the annual tax report.